Changing infant feeding practices and declining incidence of coeliac disease in West Somerset. Issue 3 (1st September 1997) - Challacombe, D N; Mecrow, I K; Elliott, K; Clarke, F J; Wheeler, E E
Abstract : An association was investigated between changing infant feeding practices and a declining incidence of childhood coeliac disease and transient gluten intolerance (TGI) in West Somerset, England during 1971–92. Dietary histories of 18 patients with coeliac disease were compared with 23 controls during 1971–80 and eight patients with coeliac disease and 39 controls during 1981–92. Our findings showed that the declining incidence of coeliac disease and TGI were associated with changing infant feeding practices, characterised by the later introduction of dietary gluten, an increased use of baby rice and gluten free foods for weaning, and an increased incidence of initial breast feeding.